Public private partnership as city project management technology - Zapivakhin Igor; Ilin Igor; Levina Anastasia (MATEC Web of Conferences, 2018)
The paper describes the principle of the public-private partnership as a mechanism for implementing infrastructure projects in cities as well as the forms of organization and financing options for such projects. The basic concepts of the public-private partnership are analyzed. The experience of implementing the public-private partnership in the framework of the project for the construction of the Moscow-Saint Petersburg interstate route is presented. The bottlenecks of the current practice of the public-private partnership were revealed. The purpose of this paper is to propose recommendations for improving the effectiveness of public-private partnership as a form of government-business relations in the Leningrad region based on an analysis of the model of public-private partnership in the region.